Implementation of Harmonious Family in the Concept of Proportionality of Obligations and Rights of Husband and Wife Relations: A Perspective on the Compilation of Islamic Law - Sar'an, Mohamad; Hidayatulloh, Yusuf; Gussevi, Sofia; Indrawan, Riski; Zuhri, Nur Alam Ullumuddin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The breakup of marriage is a permissible act, but Allah SWT does not like such a decision. In the implementation of the sakinah mawaddah and rahmah family, it is quite difficult to carry out but it is not impossible to do. The serious problem is how when a family can no longer be harmonized again to exercise rights and obligations proportionately, and whether it must end in a divorce that is hated by God. This research focuses on husband and wife to remain harmonious when carrying out obligations and rights that benefit from the perspective of KHI. This study uses a comprehensive literature study methodology based on normative legal research presenting data and facts from the perspective of compilation of Islamic law and socio-cultural phenomena of society. KHI has an important role in a legal decision process because KHI is sourced from 13 books that are complete and in accordance with the socio-cultural nature of the Indonesian state and then with the nature of Islamic law that is flexible so that it can adapt to the dynamic development of the times. Although there are several KHI rules that need to be updated, such as the tendency towards patriarchal culture because it has been a long time when it was formed, namely 33 years, it is used as a reference by legal subjects so that it can be more up-to-date again when used in more contemporary legal cases in the future.